Effect of truss retention and pruning of berry on seed yield and quality of cherry tomato (Solanum lycopersicum var cerasiforme) grown under different polyhouse structures - VIDYADHAR, BONTHA; TOMAR, B S; SINGH, BALRAJ (The Indian Journal of Agricultural Sciences, 2014)
Study was conducted to evaluate the effect of retention of truss per plant and pruning of berries per truss on seed yield and quality of cherry tomato (Solanum tycopersicum var cerasiforme L.) grown under three different polyhouse structures, viz. semi climate controlled polyhouse (P1), naturally ventilated polyhouse (P2) and insect proof nethouse (P3). Among the structures P1 gave higher berry weight (7.67 g), number of seeds/berry (60.66), 100 seed weight (0.1328 g), seed yield/berry (0.0912 g), germination (84.90%), vigour index-I (650.64), vigour index-II (1.47) and lower EC (0.0086 µS/g/cm), when compared to P2 and P3. The retention of 5 truss per plant (V1) recorded higher berry weight (7.37 g), number of seeds/berry (63.25), 100 seed weight (0.1319 g), seed yield/berry (0.0886 g), germination (84.68 %), vigour index-I (640.97), vigour index-II (1.43) and lower electrical conductivity (0.0083 µS/ g/cm), as compared to V2 and V3. The thinning of berry, i.e 10 per truss (B1) has given significantly higher mean berry weight (8.21 g), number of seeds/berry (61.53), 100 seed weight (0.1323 g), 100 seed weight (0.1323 g), seed yield/berry (0.0913 g), germination (86.01%), vigour index-I (651.96), vigour-II (1.46) and lower EC (0.0080 µS/g/ cm) in comparison to B2 and B3.